2022
DOI: 10.3389/fped.2022.945616
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve of Closed Reduction and Internal Fixation for Supracondylar Fractures of the Humerus in Children

Abstract: BackgroundThis study aimed to identify the threshold for success in supracondylar humeral fracture surgery by describing the learning curve for beginners and exploring the relationship between the learning curve and the prognosis of supracondylar fractures of the humerus.MethodsSurgical information was collected of the first 100 humeral fractures treated by four pediatric orthopedic surgeons. The relationship between operation time, wire placement success rate, and surgical experience was determined using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…These findings underscore the significance of a surgeon's experience, which directly influences outcomes, considering the notable learning curve associated with this procedure. In contrast, a recent study found no differences in adverse events at 30 days, reoperations or readmissions when comparing the performance of young and senior surgeons [12].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…These findings underscore the significance of a surgeon's experience, which directly influences outcomes, considering the notable learning curve associated with this procedure. In contrast, a recent study found no differences in adverse events at 30 days, reoperations or readmissions when comparing the performance of young and senior surgeons [12].…”
Section: Introductionmentioning
confidence: 77%
“…The authors hypothesized that the inability to successfully complete the reduction or experience of multiple unsuccessful attempts at implant placement did not affect the patient's prognosis. However, the experience accumulated from 65 operations is not the time necessary to learn the operation, but the time needed to achieve the stability of individual surgical techniques [12]. In the present series, the novice operators were supported by an experienced surgeon defined as a specialist who performed more than 15 CRPP and/or has more than 10 years of surgical experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation